Perception of injustice and embitterment in the context of social reference systems - Linden, Michael; Sandau, Elena (Advances in Social Sciences Research Journal, 2021)
Background: The “belief in a just world” psychology has shown that people across the world hold an inborn general view, that people should get what they deserve, and that malbehavior should be punished. But, what is seen as unjust is defined by social reference systems. Injustice is experienced as aggression, if not humiliation and answered by the desire to fight back, to restore justice. If the experience of injustice is paired with helplessness, a typical emotional response is embitterment which is associated with the wish for revenge, social impairment, and dysfunctional behaviors. Objective of the present study was to study the relation of conditions of living and social reference systems with perceptions of injustice, and rates of embitterment. Method: A convenience sample of 139 white and 93 black citizens from Cape Town in South Africa answered questions on their socio-economic status and changes in their lives in the past years. They also filled in the General Health Questionnaire (GHQ-12) to measure psychological distress, the Differential Life Burden scale (DLB) to assess burdens and the Posttraumatic Embitterment Disorder scale (PTED Scale), to quantify feelings of injustice and embitterment. Results: Black South Africans saw more positive changes than Whites over the past years, but nevertheless showed disadvantages in regard to education, professional qualification, employment status, and monthly income, together with significantly higher scores on the DLB, GHQ-12, and PTED scale. When looking at single items, 66.6% of black as compared to 45.3% of white participants reported about experiences evoking severe feelings of injustice, 65.4% versus 40.3% about repetitive painful memories, 53.7% versus 36.9% about an associated deterioration of well-being, and 46.2% versus 21.6% about thoughts of revenge. After controlling for monthly income, only the PTED score showed significant differences. Conclusion: Results suggest that embitterment reactions are linked to social conditions, like economic but even more so psychological factors. The results suggest that embitterment is not only of importance in individuals but can also have a societal meaning. This must be acknowledged in political discussions.